Design of array antenna for centric communication / Rajeshree Vejasegaran - Rajeshree, Vejasegaran (2017)
The main aim of this research is to design single and multi-elements on-body antennas that operate at 2.4 GHz ISM band. The patch and the ground plane are designed using highly conductive pure copper while three dielectric materials are used as the substrate for comparison purposes. The antenna design are simulated using CST Microwave Studio. Several characteristics of the antenna such as reflection coefficient, bandwidth, VSWR, efficiency and radiation pattern are evaluated for both free space and on-body application. The comparison results reveal that the antennas design using RT Duroid 5880 result in low gain loss. Only small difference in reflection coefficient, S11 and bandwidth is observed for the array antennas as a consequence of variation in body tissue thickness. The increase in the fat layer thickness also resulted in a steady increase in gain for all antenna configurations. In order to minimize the attenuation of antenna performance in close proximity with the human body, simple gain improvement techniques are utilized. Antenna simulated gain is improved by 7.2 % for the first design and 8.4 % for the second design of 2x1 array antenna and 4.7 % for 4x1 array antenna.